Photophysical properties of indicaxanthin in aqueous and alcoholic solutions. (February 2015) - Wendel, Monika; Szot, Dominika; Starzak, Karolina; Tuwalska, Dorota; Prukala, Dorota; Pedzinski, Tomasz; Sikorski, Marek; Wybraniec, Slawomir; Burdzinski, Gotard
Abstract: Photophysical properties of indicaxanthin in solution were studied at room temperature using stationary and time-resolved spectroscopies. The results obtained suggest the photoprotective role of indicaxanthin in its natural environment due to the efficient light to heat conversion, and the absence of triplet excited state formation. Transient absorption spectra were obtained for the first time for indicaxanthin in solutions. Indicaxanthin in its S1 first singlet excited state appears instantaneously upon photoexcitation at λ exc = 483 nm (S0 → S1 transition). Its band shows maximum at about λ max = 395 nm in both aqueous and alcoholic solutions. The S1 population decay can be described by a double-exponential function; the two characteristic time-constants were tentatively assigned to the presence of two stereoisomeric indicaxanthin forms. The S1 lifetimes extend in viscous solvents, from 6.5 and 31 ps in methanol to 14.1 and 161 ps in ethylene glycol. Graphical abstract: Indicaxanthin S1 state deactivation in aqueous solutions. Highlights: The S1 excited state is primarily deactivated by radiationless relaxation. Solvent viscosity affects the S1 state lifetimes and fluorescence quantum yields. Photosensitization reveals T1 excited state lifetime and absorption spectrum.